2021
DOI: 10.3389/fmicb.2021.738401
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome–Gut–Brain Axis, a Potential Therapeutic Target for Substance-Related Disorders

Abstract: Substance addiction is a complex worldwide public health problem. It endangers both personal life and social stability, causing great loss on economy. Substance-related disorder is considered to be a complicated chronic brain disorder. It resulted from interactions among pharmacological properties of addictive substances, individual susceptibility, and social–environmental factors. Unfortunately, there is still no ideal treatment for this disorder. Recent lines of evidence suggest that gut microbiome may play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 89 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…However, these results must be considered with certain reservations because other studies have found conflicting results 24 . As research progresses, the microbiota now appears as a potential therapeutic target in the management of neuropsychiatric pathologies 26,29,30 . The correlation between H 2 production and the HAD scale could also partly explain the negative correlation observed between H 2 levels and the QoL score (GIQLI score), as the latter gives high consideration to psychologic items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these results must be considered with certain reservations because other studies have found conflicting results 24 . As research progresses, the microbiota now appears as a potential therapeutic target in the management of neuropsychiatric pathologies 26,29,30 . The correlation between H 2 production and the HAD scale could also partly explain the negative correlation observed between H 2 levels and the QoL score (GIQLI score), as the latter gives high consideration to psychologic items.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the intestinal microbiota is involved in mood disorders, as clear differences have been found between the intestinal microbiota of healthy subjects and those of patients with psychiatric disorders 24 , 25 , 26 , 27 and autism. 28 In the present study, the results of anxiety and depression scales were statistically comparable between the positive and control patients.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota will become the frontier and center of disease prevention and treatment ( 84 ). Microbiological therapy may be a more comprehensive and multi-effect approach for some chronic and recurrent diseases ( 85 , 86 ). This is beneficial to the development of drugs for the treatment of DUDs.…”
Section: Discussionmentioning
confidence: 99%
“…In cigarette smokers, nicotine is classified as a substance-induced/related addition. The gut microbiome-HPA-axis is proposed as a novel therapeutic target, delivering utility bioinformatics on additive manipulation and cessation [24]. Nicotine is the pivotal toxic compound related to craving, addiction behavior, and CYP450 gene expression.…”
Section: 𝑅 =mentioning
confidence: 99%